2014
DOI: 10.1155/2014/369158
|View full text |Cite
|
Sign up to set email alerts
|

The Alterations of IL‐1Beta, IL‐6, and TGF‐Beta Levels in Hippocampal CA3 Region of Chronic Restraint Stress Rats after Electroacupuncture (EA) Pretreatment

Abstract: Immunological reactions induced by proinflammatory cytokines have been involved in the pathogenesis of depressive disorders. Recent studies showed that Electroacupuncture (EA) was able to reduce depressive symptoms; however, the underlying mechanism and its potential targets remain unknown. In the present study, we used a 21-day chronic restraint stress rats as a model to investigate how EA could alleviate depression. Open field test was carried out to evaluate the depressive symptoms at selected time points. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…The decrease in sucrose consumption is considered as the inhibition of the brain reward system [ 38 ]. The OFT has been used widely to assess the anxiety behaviors [ 39 ]; however, it also can be used to evaluate the spontaneous activity in rodents [ 34 , 40 , 41 ]. Increased immobility in the FST is often anthropomorphized as an expression of despair; however, it can also be understood as a successful and adaptive behavioral response that functions to conserve energy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease in sucrose consumption is considered as the inhibition of the brain reward system [ 38 ]. The OFT has been used widely to assess the anxiety behaviors [ 39 ]; however, it also can be used to evaluate the spontaneous activity in rodents [ 34 , 40 , 41 ]. Increased immobility in the FST is often anthropomorphized as an expression of despair; however, it can also be understood as a successful and adaptive behavioral response that functions to conserve energy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has been extensively used to treat depression in East Asian countries and has exhibited effective results in clinics. According to traditional Chinese medicine, Baihui (GV-20) and Yintang (GV-29) are points pertaining to Governor Meridian [ 34 ] and Governor Meridian has a direct contact with brain through channels and collaterals [ 41 ]. Thus, the acupoints of Baihui (GV-20) and Yintang (GV-29) are commonly used for treating depression [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on rats have shown decreased levels of pro-inflammatory cytokinesincluding tumor necrosis factor-a, interleukin-1b, and interleukin-6-after stimulation with acupuncture. [45][46][47][48][49] The underlying mechanism of these findings is unclear, but suppression of cytokine synthesis via outputs from the HPA axis has been proposed. 38 The mechanism through which acupuncture may treat chloasma (or melasma) has not been as extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…Brain and Governor Meridian have a direct contact on channels and collaterals. Based on the principle of Meridians pass, indications considered selecting Governor Meridian to treat mind illnesses related to brain, conforming to the Traditional Chinese Medicine saying “searching for the primary cause of disease in treatment.” Meanwhile, EA treatment design of our study embodies one of the most critical theories in Traditional Chinese Medicine, the principle of “treating diseases prior to its onset” which attaches great significance on disease preventions [ 55 ].…”
Section: Discussionmentioning
confidence: 99%